Occurrence of Epidermal Growth Factor Receptor Expression in Squamous Cell Carcinoma of Oral Cavity and Adjacent Sites: A Retrospective Observational Study - Dasgupta, Senjuti; Chakrabarti, Sudipta; Deb, Asit R. (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Oral cavity squamous cell carcinomas (OCSCCs) are one of the most common malignancies encountered. They have diverse clinicopathologic profiles. Epidermal growth factor receptor (EGFR) is an important marker of OCSCC for diagnosis, prognosis, and therapy.Objective The study aimed to evaluate the distribution of clinicopathological parameters in cases of squamous cell carcinoma (SCC) of the oral cavity and adjacent sites and their EGFR expression. An attempt was made to correlate EGFR scores with different parameters.Materials and Methods An observational retrospective study was undertaken for 1 year. Patients with histologically proven SCC of the oral cavity and adjacent sites were included. Clinicopathologic and immunohistochemical features of each case were analyzed.Results A total of 59 cases of SCC were included of which 41 (69%) were males. The mean age of the patients was 56.4 ± 10.3 years. The most common location of the tumors was oral cavity (31, 53%) followed by larynx (10, 16%). Most cases were moderately differentiated tumors (31, 53%). Immunohistochemical analysis showed low EGFR score in 7 (11.9%) cases, intermediate in 6 (10.1%), and high in 46 (78%) cases. Association between gender of patients and EGFR score was statistically significant (p = 0.000159). Most lesions of the oral cavity (31 cases, 53%) had a high EGFR score (23 cases, 74.2%). A statistically significant correlation was found between tumor grade and EGFR score (p = 0.03338).Conclusion This study from eastern region of India reveals unique characteristics of EGFR expression in SCC of the oral cavity and adjacent sites.
Keywords: epidermal growth factor receptor; histopathological grade; oral cavity squamous cell carcinoma